2018
DOI: 10.1093/mnrasl/sly158
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar timing constraints on the Fermi massive black hole binary blazar population

Abstract: Blazars are a sub-population of quasars whose jets are nearly aligned with the line-of-sight, which tend to exhibit multi-wavelength variability on a variety of timescales. Quasi-periodic variability on year-like timescales has been detected in a number of bright sources, and has been connected to the orbital motion of a putative massive black hole binary. If this were indeed the case, those blazar binaries would contribute to the nanohertz gravitational-wave stochastic background. We test the binary hypothesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 55 publications
(62 reference statements)
2
30
0
Order By: Relevance
“…On the other hand, Sesana et al (2018) found that if all quasi-periodic quasars involved a SBBH system, then the expected gravitational wave background at frequencies corresponding to year timescales would be in conflict with that measured with pulsar timing arrays (Foster & Backer 1990). Holgado et al (2018) similarly concluded that binarity cannot uniquely explain quasi-periodicity in the Fermi blazar population on timescales of a few years.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Sesana et al (2018) found that if all quasi-periodic quasars involved a SBBH system, then the expected gravitational wave background at frequencies corresponding to year timescales would be in conflict with that measured with pulsar timing arrays (Foster & Backer 1990). Holgado et al (2018) similarly concluded that binarity cannot uniquely explain quasi-periodicity in the Fermi blazar population on timescales of a few years.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al 2017;Chen et al 2017;Middleton et al 2018) and make statements about SMBHB population statistics (e.g. Sesana et al 2018, Holgado et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike stellar mass binary black holes (which are advanced LIGO's primary targets, e.g., Abbott et al 2016) whose detection is largely limited to the local Universe, merging BSBHs would be detectable almost close to the edge of the observable Universe (e.g., Klein et al 2016). The more massive, low-redshift population (i.e., in the relatively nearby Universe) is being hunted by pulsar timing arrays (e.g., Zhu et al 2014 Guo et al 2016;Dvorkin & Barausse 2017;Kelley et al 2017b;Mingarelli et al 2017;Wang & Mohanty 2017;Aggarwal et al 2018;Holgado et al 2018;Sesana et al 2018), whereas the less massive, high-redshift population (i.e., in the earlier Universe) will be targeted by space-borne experiments in future (e.g., Babak et al 2011;.…”
Section: Introductionmentioning
confidence: 99%